A Four-Phased Project Approach for enhancing CDIO Skills in Undergraduate Engineering Programs - R, Rajan Prakash; C, Jeyamala; D, Anitha; S, Baskar (Journal of Engineering Education Transformations, 2026)
Final-year projects are widely regarded as the capstone of engineering education, yet most institutions restrict this experience to a single-semester project, limiting student development across cognitive, affective, and psychomotor domains. To address these limitations, this study implemented and evaluated a structured four-phased project model inspired by the CDIO (Conceive–Design–Implement–Operate) framework. The model scaffolded learning through sequential phases: design thinking (conceptualization), engineering design (prototype development), capstone project (conception and design), and implementation and operation (full system realization). A mixedmethods approach was adopted, combining rubric-based assessments, pre- and post-surveys, faculty/industry feedback, and external performance indicators (publications, patents, competitions). Quantitative analyses, including descriptive statistics, t-tests, and ANOVA, revealed significantly higher performance among students in the four-phase cohort compared to those following the traditional single-project model. Descriptive results showed steady progression of rubric scores from a mean of 54.8 in Phase 1 to 74.5 in Phase 4, with reduced variability over time, indicating that the model helped weaker students improve alongside stronger peers. Survey results demonstrated consistent pre-to-post gains in motivation, teamwork, self-efficacy, and readiness, while external outcomes included nine publications, 33 patents (21 design, 12 utility), and nine competition wins— contrasting sharply with negligible outputs from traditional cohorts. The findings confirm that a scaffolded, multi-phase CDIO-inspired model enhances student learning and performance across all domains, translating academic engagement into innovation and professional readiness. This study provides empirical evidence supporting the adoption of phased capstone structures in engineering curricula, particularly in contexts where traditional single-semester models fall short.